PENGEMBANGAN DAN PENGUJIAN KINERJA TERMAL PENGERING LORONG HIBRID ENERGI SURYA-BIOMASSA TERPADU - surachman, hadi; Fachrudin, Diding; sutopo, sutopo; Sumarsono, M. (Badan Pengkajian dan Penerapan Teknologi, 2008)
Traditional methods of drying of agricultural products in Indonesian are commonly done by farmers or smallholders. The product has poor quality because of insect infestation, contamination from dirt and filth. A prototype of integrated solar-biomass hybrid tunnel drier was installed and tested at Serpong, Tangerang. In this investigation was used 44 kg tilapia mossambica fish, meanwhile the full capacity of the drier was 150 kg. The fish was initially treated with brine salt and stacked for about 12 hours before drying. The salt treated fish was dried to average moisture contents 13.34% – 14.38% w.b. from 70% w.b. in 29 hours. The fish was completely protected from rain, insects and dust. The combination of solar energy and biomass stove at low solar irradiation was able to increase the drying air 8 oC above ambient temperature.